Onomatopoeias and Word Play Found in Bilingual Children Story Books of Little Abid Series in Spiritual and General Values and Dongeng Dunia Binatang (Analysis of Translation Methods and Procedures) - Enis Fitriani; Trisnian Ifianti (Universitas Insan Budi Utomo, 2021)
The bilingual children story books have distinctive characteristics, one of them is having onomatopoeia. This qualitative descriptive study aimed to determine the translation method and procedure used in translating onomatopoeia and word play in Little Abid Series in spiritual and general values (11 books) and Seri Dongeng Dunia Binatang (7 books). In Little Abid Series in spiritual and general values the onomatopoeias or word play were expressed in the book Jujur Itu Hebat (1), Aku Bangga pada Mereka (1), and Aku Rajin Mengaji (1). In Dongeng Dunia Binatang they were expressed in the book Bebek dan Burung Hantu (2), Semut dan Lebah (1), and Rusa yang Sombong (2). The translator of Little Abid Series and translator of Dongeng Dunia Binatang in translating onomatopoeias and word play used semantic method and functional equivalence procedure because the translators wanted to emphasize the understanding of the early age readers by using words that are simple and easy to understand. Therefore, the researchers suggests that the adaptation translation method can be used to translate children’s books since in order to give maximum benefit to the readers. It means that the translators must be more creative in arranging words in the target language.